Composite External Fixators: Design with Subsequent FEM Analysis Optimization - Tomanec, Filip; Rusnakova, Sona; Kohut, Jiri; Kalova, Martina (Manufacturing Technology Journal, 2019)
An application of external fixator is a surgical method for the treatment of large bones fractures. This method has been proposed already a century ago, but despite the extensive development of science and technology, the fixator is often used in the original state of the proposal. [1] Therefore the patient and surgeons are dissatisfied with high weight and poor mobility of fixator during surgery and healing process. [2] Due to this fact it is necessary to apply new 3D technologies into this field of orthopedics and thus improve the current state of this tool. [3] In an account of this information, the 3D model of a new composite external fixator was created. In the research, the composite fixator was analyzed by the finite element method (FEM). Based on the results of FEM and the surgeon's requirements, the composite fixator was further improved and the final results show that the composite fixator proposed by the FEM is able to transfer the applied load from a patient. Therefore the data indicates that the implementation of composite material will further improve patients comfort, the healing process and the precision of surgery. Based on this fact, the mold has already been manufactured and the process of completing the product has started.
Keywords: External fixator; finite element method; composite; surgery